The readability of selected verses in the book of mark 2:1-12: Preference of Malaysian Christians between NIV and NKJV - Koh, Khai Yuan (2023)
The Bible has been around for thousands of years and has been the foundation of Christian belief even today. The Bible is a holy scripture of Christianity and Judaism that consists of both the New and Old Testaments. And it has been referred to as ‘The Word of God’ by Christians' beliefs. Throughout the centuries when scriptures have been spread across the world, many translations have been made so that people across the sea may come to understand the word. Among the translations was English, one of the most widely used languages in the world, and in this current era, there are numerous numbers of English translations of the scripture, such as the King James Version (KJV), New International Version (NIV), English Standard Version (ESV), Literal Standard Version (LSV), etc. Many debates have been held, and research has been done to determine which version of the English-translated Bible is best for believers due to the different types of their translations and the way they engage with audiences while preserving the message. In this research, usage of the NIV (New International Version) and the NKJV (New King James Version) NIV and NKJV are among the most recent English translations of the Bible, and they’re considered the best and most well-known Bible translations that have ever been used up to this day. Both versions have their own origins and unique histories that contributed to their popularity amongst the Christian community. Since both versions were created in the 1900s, the usage of the English language can be considered modern English compared to its predecessor, the KJV. The purpose of the translation was to ease modern readers comprehension of the context of the Bible and increase its readability. However, the NIV and NKJV Bibles adapt two different principles of translation, which causes readers a dilemma in determining the best version in terms of its accuracy, literature perseverance, and readability.